Emergence of New Delhi Metallo-β-Lactamase (NDM) Genes Detected from Clinical Strains of Escherichia coli Isolated in Ouagadougou, Burkina Faso - Kaboré, Boukaré; Ouédraogo, Henri S.; Zongo, Oumarou; Ouédraogo, Ganamé Abasse; Tapsoba, François; Bougma, Sanogo; Zongo, Koudbi Jacob; Zeba, Boukaré; Traoré, Yves; Sanou, Idrissa; Savadogo, Aly (International Journal of Microbiology, 2023)
The emergence and spread of carbapenem resistance in Gram-negative bacilli such as Klebsiella pneumoniae, Escherichia coli, Acinetobacter baumannii, and Pseudomonas aeruginosa through the production of carbapenemases is a global phenomenon. It threatens patient care and leads to therapeutic impasses. This study aims to genotypically determine the prevalence of the most frequent carbapenemase genes among multidrug-resistant E. coli strains isolated from patients at a biomedical analysis laboratory. A total of fifty-three unduplicated E. coli strains isolated from patient samples with a multidrug-resistant (MDR) profile were subjected to polymerase chain reaction (PCR) testing for carbapenem resistance genes. This study allowed us to identify fifteen strains carrying resistance genes among the fifty-three E. coli strains. All fifteen strains produced the metallo-β-lactamase enzymes; this represents a rate of 28.30% of study strains. Among these strains, ten carried the NDM resistance gene, NDM and VIM genes were detected in three strains and VIM was identified in two strains of E. coli. However, carbapenemases A (KPC and IMI), D (OXA-48), and IMP were not detected in the strains studied. Thus, NDM and VIM are the main carbapenemases detected in the strains in our study.